Homogeneous Discrete-Time Approximation. Issue 16 (2019) - Sanchez, Tonametl; Efimov, Denis; Polyakov, Andrey; Moreno, Jaime A.
Abstract: In this paper we study some stability properties of discrete-time systems whose transition map can be approximated by a discrete-time homogeneous transition map. This allows us to identify qualitative stability properties of discrete-time systems by only knowing the discrete-time homogeneity degree of its approximation. We show how these results can be applied to the stability analysis of discrete-time systems obtained by means of the explicit and implicit Euler discretization methods.